The surgeon-dentist's view on the "Little Tongue Test" in Primary Care: a scoping review - Vieira de Melo Bezerra, Mariana; Oliveira Bizerril, Davi; Alves dos Santos, Germana; Lima Maia, Eveline; Elizângela do Monte Almeida, Ana; Maria de Noronha Viana, Mirena; Rolim Caldas, Soraia; Gomes Bôto, Elaine; Saraiva Nogueira, Raquel; Salete Bessa Jorge, Maria (Seven Editora, 2023)
Objective: Describe through national and international literature the knowledge of the dental surgeon in relation to Ankyloglossia and the Little Tongue Test in Primary Care throughout the country. A scoping review was carried out (Joana Briggs Institute), where 07 articles published from 2011 to 2019 were selected. With mapping and analysis of the results we constituted the thematic axes: tongue test and its relationship with professionals; ankyloglossia; oral health and maternal-child network. The data showed that there is little knowledge by the professionals regarding the tongue test and ankyloglossia, and that the dentist is little included in the maternal and child network in the Primary Care setting. It was concluded that there is no integrality and insertion of the oral health team with the family health team when it comes to the maternal and child network. Furthermore, it was observed that the CD does not have enough knowledge and does not perform the Tongue Test in the Basic Health Unit. DOI: 10.56238/pacfdnsv1-042